1983
DOI: 10.1039/c39830001003
|View full text |Cite
|
Sign up to set email alerts
|

A route to 3H-1,2-diazepines by the 1,7-electrocyclisation of α,βγ,δ-unsaturated diazo-compounds

Abstract: In the thermal cyclisation of a,P;y,8-unsaturated diazo-compounds the type (6) with a cis hydrogen atom at the terminal carbon atom undergo 1,7 ring closure to give 3H-1'2-diazepines while those (9) with a methyl group at that position take an alternative reaction path to give pyrazoles via 1,5 cyclisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(38; R,R' = H and Me) derived from (E)-and (Z)-o-acetyl-Pmethylstyrenes [equation (6)]. The (E)-isomer again gave the benzodiazepine (39) (89%) while the (Z)-isomer gave only carbene products, in this case a mixture of hydrocarbons containing predominantly ( > 90%) 2,3-dimethylindene (37) as shown by comparison of its 'H n.m.r.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(38; R,R' = H and Me) derived from (E)-and (Z)-o-acetyl-Pmethylstyrenes [equation (6)]. The (E)-isomer again gave the benzodiazepine (39) (89%) while the (Z)-isomer gave only carbene products, in this case a mixture of hydrocarbons containing predominantly ( > 90%) 2,3-dimethylindene (37) as shown by comparison of its 'H n.m.r.…”
Section: Resultsmentioning
confidence: 99%
“…and more recently to monocyclic 3H-1,2diazepines. The objective of this work was to examine the reactions of the diazo compounds (4) of the same type without such a hydrogen atom but having instead a group X which it was hoped would undergo either [ 1,5]-migration (suprafacial on X) to give the 1H-benzodiazepine (6) or [1,7]-migration (antarafacial on X) to give the 3H-(7) or SH-analogue (8) (Scheme 1). A mechanistic study on a related reaction which involves cyclisation at an aromatic rather than an olefinic carbon atom has shown that the cyclisation step is an equilibrium and that the second step is a wholly intramolecular migration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the a,b,g,d-unsaturated diazoalkane 10 should emerge from 9. The 1,7-electrocyclization of such diazoalkanes to 3H-diazepines has precedent [12], which is why we propose the conversion of 10 into 11. This diazepine is considered to be the point of bifurcation of the pathway, since the 1,5-migration of the iminoacetyl group leads to the 4H-1,2-diazepines 4 and 5, whereas an allyl rearrangement with ring contraction gives rise to 6 and 7.…”
mentioning
confidence: 99%
“…In cases where it is olefinic in nature, e.g. in (2), the diazo compounds cyclise only via 1,7 closure to give 3H-1,2-diazepines, e.g. (3),2 and produce n o isolable quantities of the 3-vinylpyrazoles (1) t which would have resulted from the alternative 1,5 closure.…”
mentioning
confidence: 99%